2008
DOI: 10.1016/j.jaci.2007.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene D4 induces gene expression in human monocytes through cysteinyl leukotriene type I receptor

Abstract: Background-Cysteinyl leukotrienes (CysLTs) are important mediators of innate immune responsiveness and chronic inflammatory diseases. CysLTs acting through CysLT receptors can influence the migration and activity of cells, such as eosinophils, monocytes, and dendritic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 30 publications
6
37
1
Order By: Relevance
“…This correlates with the finding that cysteinyl LTs contribute to inflammatory reactions by induction of MCP-1 via the CCR2B receptor in THP-1 cells Woszczek et al, 2005;Hashimoto et al, 2009). This reported induction by MCP-1 was also observed in another monocytic leukemia cell line and was further supported by the enhanced activation of chemotactic activity observed in human monocytes (Woszczek et al, 2008a). Likewise, in THP-1 cells, montelukast and zafirlukast significantly down-regulated the chemotaxis induced by MCP-1 and p38 MAPK expression (Hung et al, 2006).…”
Section: Receptor Expression Patterns With Functional Significancesupporting
confidence: 58%
See 1 more Smart Citation
“…This correlates with the finding that cysteinyl LTs contribute to inflammatory reactions by induction of MCP-1 via the CCR2B receptor in THP-1 cells Woszczek et al, 2005;Hashimoto et al, 2009). This reported induction by MCP-1 was also observed in another monocytic leukemia cell line and was further supported by the enhanced activation of chemotactic activity observed in human monocytes (Woszczek et al, 2008a). Likewise, in THP-1 cells, montelukast and zafirlukast significantly down-regulated the chemotaxis induced by MCP-1 and p38 MAPK expression (Hung et al, 2006).…”
Section: Receptor Expression Patterns With Functional Significancesupporting
confidence: 58%
“…For example, in monocytes, LTD 4 induced p38 phosphorylation (Woszczek et al, 2008a), a pathway involved in the regulation of immediate-early gene expression. In a human epithelial cell line, CysLT 1 R activation has been shown to lead to either STAT-1 phosphorylation through PKC and ERK1/2 activation, causing enhanced intercellular cell adhesion molecule-1 expression and eosinophil adhesion (Profita et al, 2008), or to up-regulate mucin gene MUC2 transcription via a signaling pathway involving PKC and NF-B .…”
Section: Intracellular Signaling Pathways and Second-messenger Sysmentioning
confidence: 99%
“…Because U937 cells are a leukemia-derived cell line, we confi rmed our observation repeating some key experiments in primary HM that also have been reported to express mainly the CysLT 1 R transcript ( 44 ). We confi rmed that the LTD 4 -induced [Ca 2+ ] i transient was sensitive to montelukast and PTX (data not shown), indicating that this response is because of a CysLT 1 R activation ( 44 ) similar to the one observed in dU937 cells ( 16,29,30 ).…”
Section: Discussionsupporting
confidence: 83%
“…Blockade of leukocyte chemotaxis has been reported to alleviate EAE (31,32). It has been reported that CysLTs induce chemotactic activity in eosinophils (33) and monocytes (34). We wondered whether CysLTs also induce the chemotaxis of pathogenic T cells in EAE.…”
Section: Montelukast Blocks Ltd 4 -Induced Leukocyte Chemotaxismentioning
confidence: 95%